Development of Intensity-Duration-Frequency (IDF) Models for Manually Operated Rain Gauge Catchment: A Case Study of Port Harcourt Metropolis Using 50 Years Rainfall Data - Ogbozige, Francis James (Tanzania Journal of Engineering and Technology, 2022)
Hydraulic structures such as surface drainages and culverts are usually constructed in urban areas with the intention of draining runoff into nearby streams and rivers in order to avoid flooding. However, most of these structures frequently fail to serve the intended use due to the occurrence of high intensity rainfall accompanied with long duration, which produce runoff discharge higher than their designed capacities. This is common in many developing countries as drainages and culverts are most times constructed without considering hydrological analysis of the catchment. Hence, this research considered Port Harcourt city as a case study by utilizing 50 years rainfall data to develop rainfall Intensity-Duration-Frequency (IDF) curves that will be used for subsequent design of drainages and culverts within the city and its environs. The IDF curves were developed using Gumbel, Pearson type III and Log-Pearson type III distributions at return periods of 2, 5, 10, 25 and 50 years. However, the durations considered were 5, 10, 20, 30, 45, 60, 90, 120, 150, 180, 210, 240, 300, 360 and 420 minutes. Results showed that the IDF equations developed for the three frequency distributions highly correlate with the observed intensities since there goodness of fit (R2 ) ranges from 0.9766 €“ 0.9865. Also, it was noted that there was no significant difference (p < 0.01) between the predicted rainfall intensities from all the IDF equations and the observed intensities. Notwithstanding, the IDF equation developed for Gumbel distribution was recommended to be given higher priority since it has the highest R2 value. Keywords: Gumbel, Pearson Type III, Log-Pearson Type III, Return-Period.